SPREAD AND PREVENTION OF GOAT STRONGILIATOSIS - Rakhimberganov, Bekzod (Educational Research in Universal Sciences, 2023)
This article describes in detail the development, epizootology, disease symptoms and diagnosis of the causative agent of gastrointestinal strongylatosis of goats based on literature data.